2000
DOI: 10.15760/etd.2173
|View full text |Cite
|
Sign up to set email alerts
|

Successful Online Course Retention at Marylhurst University Constructing a Model for Online Course Retention Using Grounded Theory

Abstract: Over the past 6 years, the course retention rate for Marylhurst University's (MU) online courses was 91%, which is within four percentage points of its on-campus course retention rate (Schreck, 2002). This appears to contradict a recent article in the Chronicle of Higher Education that stated, "Although there is significant variation among institutions with some reporting course-completion rates of more than 80% and others finding that fewer than 50% of distance-education students finish their courses, several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Meeting the needs of students requires strong technical support and training faculty to create a balance between structure and dialogue. This will lead to a community of teachers-students helping students [44]. Pace University faculty members who teach in the NACTEL program regularly receive commendations from our students for their supportive, caring and effective teaching.…”
Section: Quality Policy Statementmentioning
confidence: 99%
“…Meeting the needs of students requires strong technical support and training faculty to create a balance between structure and dialogue. This will lead to a community of teachers-students helping students [44]. Pace University faculty members who teach in the NACTEL program regularly receive commendations from our students for their supportive, caring and effective teaching.…”
Section: Quality Policy Statementmentioning
confidence: 99%
“…Yet improving course completion, persistence, and success means attending to a multitude of variables. At the institutional level, Schreck explains that "strengthening the relationship between variables…is more important than improving variables in isolation….online course retention is a direct reflection of how well an institution establishes an inquiry process (i.e., how well they research, build understanding, and implement that understanding) into four major areas: courses, teachers, students, and administrative" [44].…”
Section: Factors In Online Successmentioning
confidence: 99%
“…Meeting the needs of students requires strong technical support and training faculty to create a balance between structure and dialogue. This will lead to a community of teachers-students helping students [44].…”
Section: Propositionsmentioning
confidence: 99%
“…Dissertation research has reported on student performance (Bangurah, 2004;Crabtree, 2000), the experience of student learning (Harbeck, 2001;Pedone, 2003;Schilke, 2001), student satisfaction (Aljarrah, 2000;Reed, 2001), and student retention (York, 2003). Research concerning student performance in online courses at 4-year colleges and universities is progressing along similar lines (e.g., Dupin-Bryant, 2004;Morris, Wu, & Finnegan, 2005;Schreck, 2003). For example, Schreck (2003) reported on efforts made by one university's faculty and staff to retain students in online courses.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research concerning student performance in online courses at 4-year colleges and universities is progressing along similar lines (e.g., Dupin-Bryant, 2004;Morris, Wu, & Finnegan, 2005;Schreck, 2003). For example, Schreck (2003) reported on efforts made by one university's faculty and staff to retain students in online courses. Morris et al (2005) described their work to identify student record variables that came closest to predicting retention in one university's general education online courses.…”
Section: Literature Reviewmentioning
confidence: 99%